MEMBANGUN KELUARGA INKLUSIF: SOSIALISASI PENDIDIKAN RESPONSIF GENDER BAGI MASYARAKAT NEGERI HUKURILA, KOTA AMBON - Manuputty, Feky; Pelupessy, Pieter Jacob; Litaay, Simona Christina Henderika; Haulussy, Rais Rahman; Afdhal, Afdhal; Makaruku, Nathalia Debby (Universitas Pattimura, 2025)
The family is the primary space for cultivating values of justice and gender equality. However, in Negeri Hukurila, Ambon City, family education patterns remain gender-biased. Male and female roles are often rigidly distinguished, limiting women’s voices in household decision-making and confining girls to domestik spheres while boys are encouraged toward public roles. Such conditions risk perpetuating gender inequality and hindering children’s equal development. This community service program aimed to raise public awareness of inclusive and gender-responsive family education through participatory approaches grounded in local wisdom. Methods included socialization, training, technology application, and evaluation that involving traditional leaders, saniri negeri, religious figures, youth, and women. The results demonstrate increased community understanding of gender-responsive family concepts, greater equality in family dialogue, and the revitalization of local practices such as masohi (mutual cooperation) as a symbol of just family collaboration. The novelty of this program lies in integrating local wisdom to build family education patterns that respect gender equality, positioning indigenous communities as key agents of change. The study concludes that gender-responsive family education is well accepted when delivered through culturally relevant approaches. Future recommendations include expanding cross-sector collaboration, strengthening local cadres as change agents, and encouraging community-level policies to sustain inclusive family practices